From Verbal to Audiovisual Medium: The Case of the Cinematic Adaptation of R. L. Stevenson’s Novel “The Wrong Box”. Part II - Krūminienė, Jadvyga; Višinskaitė, Indrė (Respectus Philologicus, 2018)
[straipsnis ir santrauka anglų kalba]